RUPTURE OF PENIS MUSCLE AND ITS MANAGEMENT IN GERMAN SHEPHERD DOG - RANGASAMY, S; SARATH, T; SATHIAMOORTHY, T; KULASEKAR, K (The Indian Journal of Animal Reproduction, 2023)
A German shepherd male dog with history of profuse bleeding from penis due to dog bite was diagnosed as"penis muscle rupture" and was successfully treated.
Keywords: Penis muscle; German shepherd dog; dog bite